Treatment of Dens Invagination in a Maxillary Lateral Incisor: A Case Report - Heydari, Azar; Rahmani, Mona (Iranian Endodontic Journal, 2015)
Dens invagination is a developmental anomaly requiring specific treatment approaches. Oehler’s Type III dens in dente, extends into the root and perforates at the apical area or lateral surface of the root. In this case endodontic treatment of the invaginated tooth was carried out through the central lumen of the invagination with calcium hydroxide without manipulation of the main pulp canal, thereby leaving the tooth vital. The 18-month follow-up examinations were indicative of treatment success; the periapical lesion resolved completely and the tooth remained vital. Conclusion: Information about the three dimensional anatomy of the teeth especially those with an abnormality is necessary for a successful treatment. Keywords: Apical Periodontitis; Dens Invagination; Dens Invaginatus; Dens in Dente; Invaginated Teeth; Lateral Incisor; Periapical Lesion